Spatial and seasonal diversity of wild food plants in home gardens of Northeast Thailand - Cruz García, Gisella S.; Struik, Paul C. (Springer, 2015)
Wild food plants (WFPs) are major components of tropical home gardens, constituting an important resource for poor farmers. The spatial and seasonal diversity of WFPs was analyzed across multi-species spatial configurations occurring within home gardens in a rice farming village in northeast Thailand. Data were collected in 77 sampling sites corresponding to five different home garden spatial configurations, namely fenced plot, fenced plot margin, yard, home garden boundary, and pot. Absolute abundance and frequency of occurrence were quantified per individual WFP species in both dry and rainy seasons, and data on additional uses (besides food) were collected through focus group discussions for each WFP species. A total of 20 species corresponding to 13 botanical families were reported. Results show that species abundance and frequency of occurrence varied seasonally and spatially within home gardens. Diversity, as observed in the analysis of Shannon and Simpson diversity indexes, also differed seasonally and across different spatial configurations. Home gardens showed higher diversity in the dry season because of the presence of human management. Ninety-five percent of the WFP species presented additional uses, with nine different types of uses in total. Finally, as this study demonstrates, the results on both the spatial and seasonal diversity of WFPs over different spatial configurations comprise a new perspective in home garden research by providing new understandings about their composition and management.